2016
DOI: 10.2527/jas.2015-0149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extended aging and modified atmospheric packaging on beef top loin steak color

Abstract: The objective of this study was to evaluate the effects of extended aging and modified atmospheric packaging on beef LM color. Using a randomized complete block design, each beef longissimus lumborum muscle ( = 10; USDA Choice, 3 d postmortem) was equally divided into 3 sections and randomly assigned to 1 of 3 aging periods (21, 42, or 62 d at 2°C). After respective aging, each loin section was cut into four 2.5-cm-thick steaks and randomly assigned to 1 of 3 packaging types (PVC, HiOx-MAP [80% oxygen and 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 35 publications
9
43
1
Order By: Relevance
“…However, MRA was not altered by aging for 21 d (P = 0.0973). In contrast, previous research indicated that extended aging (for 42 or 62 d) decreased MRA probably due to the depletion of reducing enzymes and mitochondrial substrates (English et al, 2016). The observed differences in MRA between our study and the previous research could be attributed to the difference in the aging days (21 vs. 42 or 62).…”
Section: Instrumental Color and Biochemical Attributescontrasting
confidence: 56%
See 2 more Smart Citations
“…However, MRA was not altered by aging for 21 d (P = 0.0973). In contrast, previous research indicated that extended aging (for 42 or 62 d) decreased MRA probably due to the depletion of reducing enzymes and mitochondrial substrates (English et al, 2016). The observed differences in MRA between our study and the previous research could be attributed to the difference in the aging days (21 vs. 42 or 62).…”
Section: Instrumental Color and Biochemical Attributescontrasting
confidence: 56%
“…However, in the present study, 7-d aged steaks had similar (P > 0.05) lightness as 14-d and 21-d aged steaks; thus, aging beyond 7 d did not increase the lightness. In contrast, English et al (2016) reported that L* values increased in beef LL aged for 62 d compared to the LL counterparts aged for 21 d.…”
Section: Instrumental Color and Biochemical Attributesmentioning
confidence: 74%
See 1 more Smart Citation
“…However, aging can also influence the initial color intensity (bloom) and the color stability of meat during subsequent retail display (Lee et al, 2008;Mancini and Ramanathan, 2014;English et al, 2016). Marino et al (2014) reported that aging can affect color, pH, and water holding capacity of meat by altering the sarcoplasmic protein patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also reported lower TBARS values in dark-cutting beef than normal-pH steaks (Sawyer et al, 2009). Increased aging time coupled with high oxygen levels in normal-pH conditions can promote lipid oxidation and decrease metmyoglobin reducing activity, leading to lower color stability in normal-pH steaks packaged in HiOx-MAP (English et al, 2016b).…”
Section: Discussionmentioning
confidence: 83%